2022
DOI: 10.24843/eja.2022.v32.i06.p10
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Literasi Keuangan, Sikap Keuangan dan Self-Efficacy terhadap Pengelolaan Keuangan Ibu Rumah Tangga

Abstract: This research is aims to determinate the effect of financial literacy and financial attitudes on homemakers financial management with self-efficacy as moderating variabel. The approach method in this reseach is the quantitative approach using the WarpPLS 7.0 analysis program. Methods of data collection using a questionnaire. The sample of this research is 148 houswives in Perumahan Green Bangil. The study result shows that financial literacy, financial attitudes, and self-efficacy have a significant effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
0
0
3
Order By: Relevance
“…Therefore, H0 is seen to be valid, indicating that "self-efficiency cannot moderate the influence of financial literacy on entrepreneurial behavior". This is in line with research conducted by [49], which states that selfefficacy cannot moderate financial literacy on housewives' financial management. It can be concluded that if students have high financial literacy but they have low selfefficacy then this will result in these students not having good entrepreneurial behavior.…”
Section: The Influence Of Financial Literacy On Entrepreneurial Behav...supporting
confidence: 91%
“…Therefore, H0 is seen to be valid, indicating that "self-efficiency cannot moderate the influence of financial literacy on entrepreneurial behavior". This is in line with research conducted by [49], which states that selfefficacy cannot moderate financial literacy on housewives' financial management. It can be concluded that if students have high financial literacy but they have low selfefficacy then this will result in these students not having good entrepreneurial behavior.…”
Section: The Influence Of Financial Literacy On Entrepreneurial Behav...supporting
confidence: 91%
“…Hasil penelitian ini tidak berbeda dengan hasil penelitan terdahulu dari (Pradinaningsih, 2022) dan (Amalia, Naili., 2022) yang menyimpulkan bahwa kepribadian berpengaruh terhadap literasi keuangan.…”
Section: Pengaruh Kepribadian Terhadap Literasi Keuanganunclassified
“…Literasi keuangan (X1) terhadap pengelolaan keuangan (Y) Pengelolaan keuangan rumah tangga oleh seorang ibu di pengaruhi oleh literasi keuangan. Literasi keuangan merupakan salah satu variabel yang dapat mempengaruhi pengelolaan keuangan (Pradinaningsih & Wafiroh, 2022). Sebagai variabel dependen perilaku seorang ibu di dalam rumah tangga di pengaruhi secara positif dan signifikan oleh literasi keuangan (Puspita, 2022).…”
Section: Hipotesisunclassified